Національному ботанічному саду ім. М.М. Гришка НАН України 70 років - Cherevchenko, T.M.; Chuvikina, N.V. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2005)
The history of creation of M.M. Gryshko National Botanical Gardens of the NAS of Ukraine, plant collection, formation of the Gardens as scientific research institution is presented. The data about scientists, who lead the Botanical Gardens in the different periods of time, is given.